Dampak Negatif Riba Terhadap Perekonomian Islam: (Perspektif Sayyid Quthb dalam Tafsir Fiy Zhilalil Qur’an) - Ersa, Ersa Al-Farizy Saragih; Oktama Putra, Fiki; Hanif, Muhammad (PAPPASANG, 2023)
The problem of usury is not a new study, because it is usury it has existed since humans knew about money, namely during the time of the Pharaohs. But the discussion is so complicated, it is still not finished yet. Especially in our country Indonesia, the actions contained therein usury, often occurs. The Islamic religious background does not allow usury, because the harm is great not only for individuals and society, but also has an impact on the economy. Reason the occurrence of usury continuously among the community, because of actions this has become a habit (culture) of mu'amalah. This research is qualitative research using description and analysis methods data. Based on data collection techniques, this research is library research (library research), using and look for written data that is qualitative description. The results of this research are an explanation of the dangers of the negative impact of usury, that usury has a very bad impact on the economy of muslims.